Role of an extensive diagnostic work-up in the detection of concealed cardiomyopathies in athletes with premature ventricular complexes and implications for sports' eligibility assessment. (25th November 2020) - Compagnucci, P; Casella, M; Guerra, F; Gasperetti, A; Volpato, G; Belfioretti, L; Riva, S; Dessanai, M.A; Pizzamiglio, F; Natale, A; Di Biase, L; Capucci, A; et al.
Abstract: Background: Premature ventricular complexes (PVCs) are a common clinical problem and a critical issue with regard to sports eligibility in sportsmen. Although PVCs can be considered a benign feature of the athlete's heart adaptive phenotype, they may also be the only clinical manifestation of a concealed cardiomyopathy, potentially heralding sudden cardiac death (SCD) during sports activity. The optimal diagnostic evaluation of athletes with PVCs is currently uncertain. Purpose: To evaluate the diagnostic contribution and the implications for sports eligibility assessment of a thorough non-invasive and invasive work-up including electroanatomical mapping (EAM) and endomyocardial biopsy (EMB) in athletes with PVCs. Methods: We conducted a prospective, single-arm, open-label double center study. All consecutive athletes presenting for evaluation at our institution after being disqualified from participating in sports due to PVCs were included in our study. These athletes underwent a baseline non-invasive diagnostic protocol with transthoracic echocardiogram and gadolinium enhanced cardiac magnetic resonance imaging (cMRI). Subsequently, an invasive diagnostic work-up was performed, including EPS with programmed electrical stimulation, EAM and EAM-guided EMB if deemed necessary. When clinically indicated, catheter ablation was performed. Sports eligibility status was re-assessed at six months' follow-up according to Italian sports medicine guidelines. Results: After diagnostic evaluation, 20 subjects out of 107 (19%) had a diagnosis of heart disease, most commonly myocarditis (n=8), arrhythmogenic right ventricular cardiomyopathy (ARVC, n=7) or dilated cardiomyopathy (DCM, n=2). On multivariate logistic-regression analysis, QRS complex/T wave abnormalities on ECG (OR 23), non left bundle branch block and inferior axis PVC morphology (OR 13), echocardiogram abnormalities (OR 24) and low-voltage areas on EAM (OR 33) were significantly associated with diagnosis of a concealed cardiac disease. Nondiagnostic abnormalities on cMRI were common in this population of athletes, prevalently involving the right ventricle. EAM-guided EMB was performed in 12 subjects (11%) and catheter ablation in 56 (52.3%). After six months, 63 athletes (59%) were judged eligible to participate in competitive sports and 23 subjects (21%) were deemed eligible to participate in non-competitive sports. Conclusions: Almost one fifth of sportsmen presenting with PVCs have a concealed heart disease, most commonly myocarditis or ARVC. Non-outflow tract PVCs' morphology and abnormalities on ECG, echocardiogram and EAM are predictive of structural heart disease's detection, whereas nondiagnostic findings on cMRI can be misleading in athletes. Invasive diagnostic tests, including EAM and EAM-guided EMB, play a critical role in case of diagnostic uncertainty. More than ¾ of subjects were judged eligible to participate in sports at 6 months' follow-up. Funding Acknowledgement: Type of funding source: None